Cervical cancer screening among reproductive-aged women: a crossectional survey in Tabanan Regency - Desak Gede Yenny Apriani; Ni Luh Putu Suariyani; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: Cervical and breast cancers are the most common malignancies among women in Indonesia. The prevalence of cervical cancer in Bali was 0.6% in 2013. Screening coverage for cervical cancer in Tabanan district varies from 37% to 67%. This study aims to determine factors associated to cervical cancer screening uptake among reproductive-aged women. Methods: A cross-sectional survey was conducted at Baturiti Subdistrict, Tabanan Regency, Bali Province. This study involved 188 reproductive-aged women. Samples were randomly selected from all reproductive-aged women from two villages of Baturiti and Angseri. Data were collected using home interviews by a standardised questionnaire. Multivariate analysis was conducted using poisson regression model to determine factors associated to cervical cancer screening uptake. Results: This study showed that the proportion of cervical cancer screening was 38.83%. Variables associated to the uptake of cervical cancer screening were comprehensive knowledge about cervical cancer (APR=10.16; 95%CI: 4.33-24.76), insurance holder (APR=2.95; 95%CI: 1.38-6.64) and aged of ≥40 years (APR=1.26; 95%CI: 1.01-1.59). Education level, employment status and perceived benefits were not associated with the screening uptake among reproductive-aged women. Conclusions: Level of knowledge about cervical cancer, insurance ownership and aged over 40 years increase the cervical screening uptake among reproductive-aged women.